Spatial analogies pervade complex relational reasoning: Evidence from spontaneous gestures - Cooperrider, Kensy (Cogn Res Princ Implic, 2016)
How do people think about complex phenomena like the behavior of ecosystems? Here we hypothesize that people reason about such relational systems in part by creating spatial analogies, and we explore this possibility by examining spontaneous gestures. In two studies, participants read a written lesson describing positive and negative feedback systems and then explained the differences between them. Though the lesson was highly abstract and people were not instructed to gesture, people produced spatial gestures in abundance during their explanations. These gestures used space to represent simple abstract relations (e.g., increase) and sometimes more complex relational structures (e.g., negative feedback). Moreover, over the course of their explanations, participants’ gestures often cohered into larger analogical models of relational structure. Importantly, the spatial ideas evident in the hands were largely unaccompanied by spatial words. Gesture thus suggests that spatial analogies are pervasive in complex relational reasoning, even when language does not.